Internationalizing Higher Education
XVI, 260 p.
Keywords: "Higher education is facing unprecedented change as today’s graduates need particular skills, awareness, and knowledge to successfully navigate a complex and interconnected world. Higher education institutions and practitioners are under pressure to be attentive to internationalization initiatives that support increasingly diverse student populations and foster the development of global citizenship competencies which include, “problem-defining and solving perspectives that cross disciplinary and cultural boundaries” (Hudzik, 2004, p. 1 as cited in Leask & Bridge, 2013). Internationalizing Higher Education: Critical Collaborations across the Curriculum is for current and future faculty, student affairs staff, and administrators from diverse disciplinary, institutional, and geographic contexts. This edited volume invites readers to investigate, better understand, and inform intercultural pedagogy that supports the development of mindful global citizenship. This edited volume features reflective practitioners exploring the dynamic and evolving nature of intercultural learning as well as the tensions and complexities. Contributors include institutional researchers, directors and key implementers of EU/Bologna process in Poland (one of the newest members and one that is facing unprecedented change in the diversity of its students), international partners in learning abroad programs, and scholars and instructors across a range of humanities, STEM, and social sciences.".